Fatal tracheal aspergillosis during rituximab combined chemotherapy for diffuse large B‐cell lymphoma that developed after lung transplantation. Issue 6 (13th November 2015) - Kawamoto, K.; Shibasaki, Y.; Sato, S.; Nemoto, H.; Takizawa, J.; Narita, M.; Tsuchida, M.; Sone, H.; Masuko, M.
Abstract: Invasive tracheal aspergillosis (ITA) is an infection that is unique to patients who have undergone lung transplantation (LT). Although the activity of this disease often appears on imaging, we encountered a case of ITA that became exacerbated, despite few computed tomography (CT) findings, during rituximab combined chemotherapy for diffuse large B‐cell lymphoma. ITA developed during immunosuppressive therapy after LT. Because CT findings may show false‐negative results, bronchoscopy is recommended for such cases.